Post-Discharge Services and Psychiatric Rehospitalization Among Children and Youth - James, Sigrid (2010)
This study examined risk and determinants of rehospitalization of children and adolescents (n = 186) following a first psychiatric hospitalization. It specifically examined the role of post-discharge services. Data were collected for a 30-month follow-up period through structured telephone interviews with caregivers and case record abstractions. 43% of youth experienced readmissions during the follow-up period. Risk of rehospitalization was highest during the first 30 days following discharge and remained elevated for 3 months. 72% of youth received 284 post-discharge services during the follow-up period, which significantly reduced the risk of rehospitalization. Longer first hospitalizations and a higher risk score at admission increased risk.